Intra-aortic balloon occlusion for refractory cardiac arrest in a patient with anterior myocardial infarction - YILDIRIM, ÇAĞAN; UYSALER, EREN; NİZAM, AHMET CEM; ATAŞ, HALİL; TİGEN, MUSTAFA KÜRŞAT; MUTLU, BÜLENT (My University, 2022)
Despite recent advances in its management, the outcome of cardiac arrest is often poor despite appropriate cardiopulmonary resuscitation. The arteriovenous perfusion gradient achieved dur ing cardiopulmonary resuscitation is associated with the successful return of spontaneous cir culation. Continuous balloon occlusion of the descending aorta is an experimental method that can occlude the \"unnecessary\" part of the circulation, thus diverting generated pressure and blood flow to the heart and brain. In this study, we present a case report of a patient unre sponsive to standard cardiopulmonary resuscitation, in whom constant intra-aortic balloon occlusion achieved a return of spontaneous circulation and successful survival.

Tedavisindeki son gelişmelere karşın, kalp durmasının sonlanımları uygun yapılan kardiyopulmoner resüsitasyona rağmen halen çok kötüdür. Kardiyopulmoner resüsitasyon sırasında oluşturulan atreiyovenöz basınç gradiyenti spontan dolaşım dönüşü ile ilişkilidir. İnen aortanın balon ile sürekli oklüzyonu dolaşımın “gereksiz” kısmının çıkartıldığı ve böylece oluşturulan basınç ve kan akımının kalp ile beyine yönlendirildiği deneysel bir yöntemdir. Bu çalışmada, standart kardiyopulmoner resüsitasyona yanıtsız olan ve sürekli intraaortik balon oklüzyonu ile spontan dolaşımın geri döndürülebildiği, sonrasında da başarılı sağkalımın sağlandığı bir olguyu sunuyoruz.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Cardiopulmonary resuscitation; myocardial infarction; percutaneous coronary intervention; resuscitative endovascular aortic occlusion; sudden cardiac death; Ani kardiyak ölüm; kardiyopulmoner resüsitasyon; miyokart enfarktüsü; perkütan koroner girişim; resüsitatif endovasküler aortik oklüzyon